The neurological manifestations in children with COVID-19 infection - Ahmed Abdul Hadi Mohsen; Alaa Abdul Muslim Kadhim; Hiba Sadiq Mohammed Hassan; Jasim Mohamed Hashim Al Mosawy; Alaa Jumaah Manji Nasrawi (Zaslavsky O.Yu., 2024)
Background. Children infected with COVID-19 may experience a variety of neurological symptoms. During the outbreak of COVID-19, doctors should consider SARS-CoV-2 infection as a differential diagnosis when meeting patients with neurological symptoms. This study aims to investigate the neurological symptoms of COVID-19 infection. Materials and methods. A cross-sectional study enrolled 100 patients (age range from 1 month to 12 years) admitted to the emergency room with neurological symptoms between October 1, 2020, and August 1, 2021. Results. Sixty out of 100 patients were positive for COVID-19 that was confirmed by polymerase chain reaction. Eighteen (30 %) children had lower limb weakness and abnormal gait, fit was detected in 12 (20 %) cases, a disturbed level of consciousness - in 18 (30 %), and Guillain-Barre-like syndrome - in 12 (20 %); the outcome was favorable in almost all patients. Overall, neurological manifestations were more common in school-age children than in other age groups (p-value of 0.01). Conclusions. We presented these cases to highlight the link between COVID-19 and neurological manifestations, as it was found that while a disturbed state of consciousness is common among school-age children, convulsions are more common in infancy.